Last night at the Telegraph Club - Lo, Malinda (Dutton Books, 2021)
"Seventeen-year-old Lily Hu can't remember exactly when the question took root, but the answer was in full bloom the moment she and Kathleen Miller walked under the flashing neon sign of a lesbian bar called the Telegraph Club. America in 1954 is not a safe place for two girls to fall in love, especially not in Chinatown. Red-Scare paranoia threatens everyone, including Chinese Americans like Lily. With deportation looming over her father--despite his hard-won citizenship--Lily and Kath risk everything to let their love see the light of day"--